Characterizing the Alabastro listato or fiorito of Hierapolis in Phrygia: A Simple Method to Identify its Provenance using Carbon Stable Isotopes. (25th May 2017) - Brilli, M.; Giustini, F.; Barone, P. M.; Fayek, A.; Scardozzi, G.
Abstract : Alabastro listato or fiorito of Hierapolis in Phrygia was a prestigious coloured marble widely used in Roman architecture and decoration. This stone is generally identified in artefacts on autoptic examination, but it may sometimes be confused with alabasters of different provenances. This study describes a simple, but effective, scientific method to contribute to the determination of Hierapolis alabaster. Due to its unique genetic context, it is characterized by a distinctive carbon isotope signature. A comparison between the stable carbon isotope data from this paper and from the literature confirms the uniqueness of the isotopic character of Hierapolis alabaster. Carbon isotopes can ensure a reliably provenance attribution of the alabaster artefacts along with visual recognition by an expert eye.